Hydrogels in Burn Wound Management—A Review - Agnieszka Surowiecka; Jerzy Strużyna; Aleksandra Winiarska; Tomasz Korzeniowski (Gels, 2022)
Inert hydrogels are of a great importance in burn first aid. Hydrogel dressings may be an alternative to cooling burn wounds with streaming water, especially in cases of mass casualty events, lack of clean water, hypothermia, or large extent of burns. Hydrogels that contain mostly water evacuate the heat cumulating in the skin by evaporation. They not only cool the burn wound, but also reduce pain and protect the wound area from contamination and further injuries. Hydrogels are ideally used during the first hours after injury, but as they do not have antimicrobial properties per se, they might not prevent wound infection. The hydrogel matrix enables incorporating active substances into the dressing. The active forms may contain ammonium salts, nanocrystal silver, zinc, growth factor, cytokines, or cells, as well as natural agents, such as honey or herbs. Active dressings may have antimicrobial activity or stimulate wound healing. Numerous experiments on animal models proved their safety and efficiency. Hydrogels are a new dressing type that are still in development.